Pengaruh Penerimaan Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Pada Pemerintah Daerah Kabupaten/Kota Di Provinsi Lampung Periode 2010-2013 - Apip Alansori; Muhammad Luthfi; Hardini Ariningrum (Universitas Malahayati, 2017)
Regional economy development is a starting point of development, and the region isexpected to recognize its potentials and needs.This research used statistical analysis withSPSS 16 software. Samples were 10 districts from 14 districts/municipals in Lampungprovince. Data this research was taken from 2010-2013. Data were taken from report ofbudget realization of districts/municipals in Lampung province provided by Statistic Office ofLampung province. Collected data were analyzed with classic assumption test and thenhypothesizes were tested with double linier regression, t-test, f-test, and coefficient ofdetermination. The result of t-test showed that the regional tax had significance value of0.653 > 0.05 and tcount 0.463 < ttable 2.0017. Regional retribution has significance value of0.000 < 0.05 and tcount 11.155 <ttable 2.0017. f-test result showed significance value of 0.812 >0.05 and f-count 0.000 < f-table 3.15. The conclusion was that regional tax partially did notinfluence, and regional retribution influenced negatively, the regional original income.Simultaneously, regional tax and regional retribution influenced regional original income.